Galanginin Protects AML-12 Cells Against Dactinomycin Induced Hepatotoxicity - Melek AKINCI; Çağatay OLTULU; Elvan BAKAR; Zatiye Ayça ÇEVİKELLİ YAKUT (Namık Kemal Tıp Dergisi, 2023)

(untitled)
Aim:The purpose of this study was to evaluate the effects of galanginin (Gal) on dactinomycin induced hepatotoxicity in vitro.Materials and Methods:AML-12 cell line was divided into 4 groups as the control, Gal, dactinomycin, and Gal+dactinomycin groups. IC50 dose was determined by the thiazolyl blue tetrazolium bromide test. Gene expressions of glutathione (GSH), superoxide dismutase (SOD), catalase, caspase 3 (Cas-3), Cas-9, apoptotic protease activating factor-1 (Apaf-1), B cell CLL/lymphoma-2 (Bcl-2), Bcl-2 associated X protein (Bax), tumor protein p53 (p53), second mitochondria-derived activator of caspase/direct inhibitor of apoptosis-binding protein (smac/DIABLO), topoisomerase (Top) I, and Top II were determined with quantitative real-time polymerase chain reaction analysis.Results:Dactinomycin elevated the expression of SOD, catalase, and GSH in response to oxidative effects. In the Gal+dactinomycin group, Gal administration reduced Apaf-1 expression and increased Bcl-2 expression with antiapoptotic effects. In the dactinomycin group, p53 levels increased due to the defense mechanism against DNA damage. Gal increased smac/DIABLO expression to remove damaged structures. Bcl-2 and smac/DIABLO expression levels in the groups were inversely proportional. In the Gal+dactinomycin group, Top II expression level was lower than in the dactinomycin group. This result indicated that double strand of DNA damage was diminished by Gal.Conclusion:Gal protected against the hepatotoxicity due to dactinomycin with antioxidant and antiapoptotic effects. Further experimental studies are needed to establish the use of Gal in liver damage.